THE EFFECT OF CELEBRITY ENDORSEMENT ON PURCHASE INTENTION - Tarigan, Ruth Srininta; Tandung, Juliana Caesaria; Sutrisno, Ansell Kevyn; Viriyani, Viriyani (Petra Christian University, 2023)
The utilization of celebrity endorsement as a marketing strategy has gained widespread popularity across various industries, including the electronic industry. The objective of this study is to assess the correlation between celebrity endorsement and purchase intention, specifically through brand image. The analysis compares the relationship between variables at two levels: industry and brand, each at varying levels of maturity. Results indicate that at the industry level, brand image plays a positive mediating role in the relationship between celebrity endorsement and purchase intention, despite a negative direct relationship between the two. At the brand level, celebrity endorsement has a negative impact on purchase intention for Samsung, while exhibiting no significant effect on Vivo brand. However, brand image positively mediates the relationship between the two. Furthermore, multigroup analysis reveals that the difference in effect between the two brands is not statistically significant.